Factors Influencing Interest in Continuing Use of e-Wallet Using the Technology Acceptance Model and Task-Technology FIT - Nandinar Adritanaya Narendrar; Jatmiko Endro Suseno; Dinar Mutiara Kusumo Nugraheni (Mimbar Ilmu, 2023)
An electronic wallet (e-Wallet) application allows users to make transactions electronically by storing user money on a server. The use of e-wallets is increasing daily, increasing the number of transactions and users. This research aims to analyze the factors related to the intention to reuse e-wallet applications so that they can contribute to the development of e-wallet applications. This quantitative research combined the Technology Acceptance Model and Task-Technology Fit models using the PLS-SEM method and SmartPLS software. Data was collected using a Likert scale questionnaire based on Google Forms. Data analysis technique using inferential statistical analysis. The research results obtained after testing the Outer Model, Inner Model, and Hypothesis Testing show that task characteristics, technological characteristics, task and technology suitability, and users' perceived usability significantly influence the intention to reuse e-wallet applications. The user's perceived ease of use factor does not significantly influence the intention to reuse the e-wallet application. Based on the results obtained, this study has a high predictive relevance value, thus confirming that the combination of the TAM and TTF models has an effective theoretical basis for analyzing the sustainable interest of e-wallet applications.